2017
DOI: 10.15540/nr.4.1.37
|View full text |Cite|
|
Sign up to set email alerts
|

Combined Neurofeedback and Heart Rate Variability Training for Individuals with Symptoms of Anxiety and Depression: A Retrospective Study

Abstract: Introduction.Neurofeedback (NFB) and heart rate variability (HRV) training present promising, nonpharmaceutical intervention strategies for anxiety and depression. This report is the first to address whether concurrent NFB and HRV (NFB+HRV) provides a viable intervention for symptoms of anxiety and depression, measured by the Achenbach System of Empirically Based Assessment (ASEBA) questionnaire. Methods. 183 children and adults with symptoms of anxiety and/or depression underwent NFB+HRV training. Psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…This initial group of individuals excluded employees and family members of employees, due to potential conflict of interest. Further exclusion criteria for this study were: total time to complete the program was fewer than six weeks or more than 24 weeks (our center recommends that clients complete the 30-session program in 12 weeks (White et al 2017)), IVA results consistent with a potential neurodevelopmental or neurocognitve disorder (as identified by the IVA + Plus Interpretive Flowchart for ADHD, version 2014.2), and ASEBA scores that indicated the client was denying or exaggerating the existence of problems (as defined by the ASEBA, for children: a Total Problems raw score less than 3 or more than 133; for ages 18-35: less than 9 or more than 142; for ages 36–59: less than 7 or more than 100). After exclusion criteria were applied, 139 clients remained in the current analysis.…”
Section: Methodsmentioning
confidence: 99%
“…This initial group of individuals excluded employees and family members of employees, due to potential conflict of interest. Further exclusion criteria for this study were: total time to complete the program was fewer than six weeks or more than 24 weeks (our center recommends that clients complete the 30-session program in 12 weeks (White et al 2017)), IVA results consistent with a potential neurodevelopmental or neurocognitve disorder (as identified by the IVA + Plus Interpretive Flowchart for ADHD, version 2014.2), and ASEBA scores that indicated the client was denying or exaggerating the existence of problems (as defined by the ASEBA, for children: a Total Problems raw score less than 3 or more than 133; for ages 18-35: less than 9 or more than 142; for ages 36–59: less than 7 or more than 100). After exclusion criteria were applied, 139 clients remained in the current analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Neurofeedback is also a form of biofeedback that is showing promising effects in correcting negative symptoms including depression (Cheon et al, 2015), sleep disorders (Cheon et al, 2015), attention-deficit/hyperactivity disorder (Van Doren et al, 2019), and anxiety (Cheon et al, 2015;Kerson, Sherman, & Kozlowski, 2009;Scheinost et al, 2013;Wang et al, 2019;Zhao et al, 2018). In addition, combinations of neurofeedback and biofeedback (e.g., HRV) have produced promising outcomes for reducing anxiety symptoms (White et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In conjunction with breath control, neurofeedback training has been shown to be a promising mitigatory tool for anxiety. For example, White et al [43] demonstrated that breathing-based visual neurofeedback reduces symptoms in patients with anxiety and depression, while acoustically-mediated deep breathing neurofeedback was shown by Crivelli et al [44] to diminish long-term stress and anxiety levels in young adults. The first step towards an EEG-based BCI able to monitor anxiety levels, to identify an individual's optimal breathing patterns, and to adapt breathing entrainment parameters in real-time, is to determine whether anxiety can be classified on the basis of ongoing EEG data.…”
Section: Introductionmentioning
confidence: 99%